TEOLOGI BURUH: Agama dan Sikap Pasrah Perempuan Buruh Sanggan Batik - Rita Rahmawati; M. Muslih Husein; Asmuni Hayat (JURNAL PENELITIAN, 2014)
This qualitative descriptive research aimed to describe in detail the meaning of the values of religion and the expression of women's resignation among batik workers in the struggle of the production process, and the factors that influence it. The research took place in Pekalongan City and data were obtained through observation, interviews, and literary studies. The results showed that a deep belief in God is the foundation of understanding the value of religion in the world of work as well as when they interact with the skipper and other workers. The expression of resignation is seen in almost all stages, from raw material procurement and production to marketing. The surrender of women workers is also evident in labor relations and outside the employment relationship, which is due to the fact that the religious elite is the skipper and the social conditions of a patriarchal religious culture.